The great unexpected eaudiobook - Creech, Sharon (Recorded Books Inc., 2012)
A Newbery Medal winner and Honor recipient, Sharon Creech is beloved by young listeners for tales brimming with humor and drama. A story of friendship and forgiveness, The Great Unexpected stars two orphan girls, Lizzie and Naomi- friends with very different personalities who embark on a series of quirky adventures in the small town of Blackbird Tree. Along the way, they make a new friend and discover shocking secrets about their past.